Pengaruh Budaya Organisasi Dan Motivasi Kerja Terhadap Kinerja Karyawan Techno Boutique Malang - Anugrah, Roy (Fakultas Ekonomi Universitas Wisnuwardhana, 2019)
This study aims is to determine the influence of organizational culture and motivation and its impact on employee performance at Techno Boutique Malang. The data is primary data by sampling samples in this study were 39 employees at Techno Boutique Malang. Sampling technique in this study using census data in this research will be obtained directly from the results of the questionnaire. The analytical tool used Test Instrument Research, analysis and regression lines by t test. t-test results showed Cultural organizations has a significant effect on employee performance. Employee motivation has significant effect on employee performance. Keywords : organizational culture, motivation compensation, employee performance